Risk factors for bleeding after endoscopic submucosal dissection of colorectal neoplasms - Suzuki, Sho (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the risk factors for delayed bleeding following endoscopic submucosal dissection (ESD) treatment for colorectal neoplasms. METHODS: We retrospectively reviewed the medical records of 317 consecutive patients with 325 lesions who underwent ESD for superficial colorectal neoplasms at our hospital from January 2009 to June 2013. Delayed post-ESD bleeding was defined as bleeding that resulted in overt hematochezia 6 h to 30 d after ESD and the observation of bleeding spots as confirmed by repeat colonoscopy or a required blood transfusion. We analyzed the relationship between risk factors for delayed bleeding following ESD and the following factors using univariate and multivariate analyses: age, gender, presence of comorbidities, use of antithrombotic drugs, use of intravenous heparin, resected specimen size, lesion size, lesion location, lesion morphology, lesion histology, the device used, procedure time, and the presence of significant bleeding during ESD. RESULTS: Delayed post-ESD bleeding was found in 14 lesions from 14 patients (4.3% of all specimens, 4.4% patients). Patients with episodes of delayed post-ESD bleeding had a mean hemoglobin decrease of 2.35 g/dL. All episodes were treated successfully using endoscopic hemostatic clips. Emergency surgery was not required in any of the cases. Blood transfusion was needed in 1 patient (0.3%). Univariate analysis revealed that lesions located in the cecum (P = 0.012) and the presence of significant bleeding during ESD (P = 0.024) were significantly associated with delayed post-ESD bleeding. The risk of delayed bleeding was higher for larger lesion sizes, but this trend was not statistically significant. Multivariate analysis revealed that lesions located in the cecum (OR = 7.26, 95%CI: 1.99-26.55, P = 0.003) and the presence of significant bleeding during ESD (OR = 16.41, 95%CI: 2.60-103.68, P = 0.003) were independent risk factors for delayed post-ESD bleeding. CONCLUSION: Location in the cecum and significant bleeding during ESD predispose patients to delayed post-procedural bleeding. Therefore, careful and additional management is recommended for these patients.